Application of diazonium chemistry in purine modifications: A focused review. (9th August 2021) - Sengupta, Saumitra; Das, Parthasarathi
Abstract : Deaminative modifications of purines via diazonium chemistry have long been the cornerstone in modified nucleoside synthesis. The purpose of this review is to bring into focus the impact of dediazoniative methods such as non‐aqueous Sandmeyer halogenations, fluorination, arylation, and carbon‐heteroatom bond formations on natural purines and their nucleosides as versatile tools for purine modifications en route to various nucleoside drugs, drug discovery scaffolds, and adducted oligonucleotides of biomedical interests. Metal free reactions of arenediazonium salts with purine nucleosides for the synthesis of 8‐aryl purines, in particular, 8‐aryl guanosines and photochromic 8‐arylazo purines are also highlighted. The treatise is expected to create broad interest among organic and biological chemists for further explorations in this area. Abstract : Modification of purine bases and nucleosides using diazonium chemistry is reviewed.